Access to Healthcare among People with Physical Disabilities in Rural Louisiana. Issue 3 (15th April 2016) - Davidsson, Nina; Södergård, Björn
Abstract : The aim was to explore the perceptions about factors that impede and facilitate access to healthcare among rural residents in Louisiana with physical disabilities. The participants were recruited through local churches and word of mouth. Nine in-depth interviews were conducted. The interviews were analyzed using content analysis. Seven categories containing barriers and facilitators were found. The interviewees described lack of transportation, lack of specialized care locally, limits in insurance coverage, lack of financial resources, and lack of knowledge about health care to be the main barriers. The main facilitators were social support, mainly from family and friends, transportation assistance, continuity of care, trust in doctors, and insurance coverage. People with disabilities in rural areas face several barriers when accessing health care but also multiple facilitators. A group that was identified as particularly vulnerable were low-income households that were not eligible for Medicare/Medicaid but still had high expenditures on health care due to disabilities.